Obstetric profiles of foreign-born women in Western Australia using data linkage, 1998-2006 - von Katterfeld, B.; Li, Jianghong; McNamara, Beverley; Langridge, A. (Blackwell Publishing, 2011)
Background:  Despite Western Australia (WA) having the highest proportion of overseas-born residents of any Australian state, no previous study has examined the general patterns of obstetric health of foreign-born women in WA. Aims:  To examine the obstetric profiles of foreign-born women in WA using routinely collected perinatal data. Methods:  The records of 59 245 confinements to foreign-born women were compared with those of 149 737 Australian-born, non-Indigenous women in WA between 1998 and 2006 using chi-square tests and ANOVA procedures. Results:  Foreign-born women were generally older, more likely to be married and have partners in highly skilled occupations, and were less likely to have private insurance or be teenage mothers. They were more commonly grand multiparae and were more likely to give birth at age 35 or older. On average, foreign-born women experienced increased risk of gestational diabetes, pre-labour rupture of membranes, failure to progress, fetal distress, perineal laceration and post-partum haemorrhage. They were less likely to have an induced labour and more likely to use fetal monitoring. Instrumental delivery, episiotomy and caesarean sections varied with maternal region of origin. Conclusions:  Several important differences in the obstetric profiles of foreign-born women were found. These differences have useful implications for obstetric services in culturally and linguistically diverse populations. Collection of further variables would also benefit the future provision of equitable and culturally appropriate care to diverse immigrant groups.